Metodologia educativa na formação de bons hábitos alimentares em escolas na cidade de Belém-Pa - SILVA, Fernanda da Costa (2023)
This research attempted to describe the experience of an educational methodology applied to students in the fifth year from a public and a private school, in the city of BelémPA. The study is of the crosssectional type, based on an educational intervention achieved in four steps: 1) application of an individual test about food and healthy habits; 2) expository and dialogical classes about food categories, food groups, the act of eating and the 10 steps to an adequate and healthy nutrition, all of which were dealt with in the Guia Alimentar para a População Brasileira (2014) (Nutritional Guide to the Brazilian Population (2014)); 3) the carrying out of methods for memorizing (question and answer game and construction of the food stoplight); 4) reapplication of the test. It was observed that all the private school students had a better performance on the second test, while 34,8% of the public school students achieved unsatisfactory results. The children appeared interested, participated actively and were capable of expressing a critical view about their eating habits. In the memorizing activities, the classes that were evaluated answered all the questions correctly, demonstrating that they were able to absorb the content that was taught. In light of this, it is concluded that this methodology was a happy, creative and less tiring strategy of teaching in class, in which the ludic use has favored an uncomplicated learning for both classes.